Determinants of job stress among middle-level administrators in institutions of higher learning in the Philippines - Djaleta, Negero (1984)
A total of 205 deans, assistant deans, directors and registrars from 15 sectarian and non-sectarian complex tertiary institutions in Metro Manila indicated moderate levels of job stress as measured by perceived job tension and self-reported physical and behavioral disorders. Organizational structures and organizational change, job factors (role conflict, work overload, responsibility for people, working conditions, and the pressure), work group factors, some personality factors, and higher-order need strength were positively related to all indices of job tension while managerial competence was inversely correlated to these indices. The three measures of job stress were positively related to each other.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Keywords: Job stress; School administrators -- Job stress; Work -- Psychological aspects